2012
DOI: 10.1016/j.ejmech.2011.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Analogues of doxanthrine reveal differences between the dopamine D1 receptor binding properties of chromanoisoquinolines and hexahydrobenzo[a]phenanthridines

Abstract: Efforts to develop selective agonists for dopamine D1-like receptors led to the discovery of dihydrexidine and doxanthrine, two bioisosteric β-phenyldopamine-type full agonist ligands that display selectivity and potency at D1-like receptors. We report herein an improved methodology for the synthesis of substituted chromanoisoquinolines (doxanthrine derivatives) and the evaluation of several new compounds for their ability to bind to D1- and D2-like receptors. Identical pendant phenyl ring substitutions on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It has been reported that the restricted conformation of the β-phenyl-dopamine pharmacophore renders the selectivity and full agonism at D1R of catechol D1R agonists. 36 Here, we expanded on this finding and revealed a differential activation profile of DHX, m-DHX, and DOX at two homologous G protein subtypes , Gαs and Gαolf. While these compounds exerted full agonism at Gαs, they behaved as partial agonists at Gαolf.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It has been reported that the restricted conformation of the β-phenyl-dopamine pharmacophore renders the selectivity and full agonism at D1R of catechol D1R agonists. 36 Here, we expanded on this finding and revealed a differential activation profile of DHX, m-DHX, and DOX at two homologous G protein subtypes , Gαs and Gαolf. While these compounds exerted full agonism at Gαs, they behaved as partial agonists at Gαolf.…”
Section: Discussionmentioning
confidence: 81%
“…In this study, we investigated a series of D1R agonists with diverse structures from both catechol (dihydrexidine (DHX), methyl-dihydrexidine (m-DHX), doxanthrine (DOX)) 36 and non-catechol (tavapadon (TAV), PF-8294, PF-6142) 19 classes. Unlike the control compounds (i.e., DA, SKF38393, SKF81297), there was a discernible difference in the efficacy of these agonists, relative to DA, at Gα s and Gα olf .…”
Section: Resultsmentioning
confidence: 99%
“…Arylation of the N -methoxyamide derived from alanine with a variety of heterocyclic aryl iodides on gram scales to make various unnatural amino acids was also demonstrated. These unnatural amino acid intermediates were further transformed to drug molecules such as a human kynurenine aminotransferase (KAT) II inhibitor 11 and Doxanthrine, 12 as well as chiral hydroxamic acid ligands 13 and a variety of new chiral pyridine-2,6-bis(oxazolines) (PyBOX) ligands 14 (Figure 2). …”
Section: Introductionmentioning
confidence: 99%